PENGARUH PAJAK AIR PERMUKAAN TERHADAP PENDAPATAN ASLI DAERAH DI BAPENDA P3DW I RANCAEKEK - Vina, Vina Robi Nawawiyah; R. Deden Adhianto (JEBS (Journal of Economic and Business Student), 2024)
Taxes are one of the main sources of state income in Indonesia. This research aims to determine the effect of surface PAP on PAD in Bapenda I Rancaekek with a research observation period in 2022. This research was carried out by going directly to the research site by participating in the PKL program. The population of this research is reports of PAP and PAD receipts at Bapenda I Rancaekek for the period 2022. The sample in this study is the realization of PAP and PAD receipts at Bapenda I Rancekek in 2022. The data used in this research is technical secondary data, the data analysis used is simple linear regression, with the help of SPSS Version 26 for Windows. The results of this research show that the PAP variable with a sig. 0.200 > 0.05 has an effect on PAD. The level value (R2) of 0.987 has a very strong relationship between the independent variable and the dependent variable. Based on the discussion, the conclusion of this research is that if PAP revenues increase, then PAD will increase, and vice versa. It is recommended that local governments further increase socialization about PAP in order to increase PAD revenues at Bapenda I Rancaaekek.